Pengaruh Model Pembelajaran Problem Based Learning Terhadap Keterampilan Menulis: Literature Review - Gautama, Rolli (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2025)
Learning models are crucial instruments in education as they directly impact student learning outcomes. Among various pedagogical innovations, Problem Based Learning (PBL) has emerged as a highly effective model for writing instruction. This study aims to comprehensively describe the application of the Problem Based Learning model in improving students' writing skills through a systematic literature review. The research method employed is Literature Review (LR). The data criteria include scientific articles from Sinta 1 to Sinta 6 accredited national journals published within the last ten years (2015–2025). In the initial search phase using specific keywords, 60,800 articles were identified. The selection process was then tightened through title validation and elimination based on topical relevance, leaving 15 articles. After a quality review conducted by reading the full texts to ensure alignment with the research focus, 10 final articles were selected as the primary data sources. The review results indicate that the Problem Based Learning model significantly enhances students' writing skills across various educational levels. The implementation of PBL successfully transforms previously passive students into active and collaborative participants in the creative process. Significant improvements were observed in writing various text types, including argumentative, explanatory, observation reports, descriptive, news, and negotiation texts. Consequently, this model is highly recommended for language instruction.